Urban green and its relation with air pollution: ecological studies in the Metropolitan area of Rome (Italian Journal of Public Health, 2008)
Tropospheric ozone (O3) and Particulate Matter (PM) have become a major concern in mostEuropean cities. In particular, in Italy the O3 concentrations exceed the limits established for the protection ofboth human health and vegetation. More integrative studies are revealing that urban trees could concretelyhelp in improving air quality, not only because of their well known aesthetic and recreational benefit, but alsofor their capability to reduce air temperature and to remove air pollutants. This reduction takes place bothdirectly, by dry deposition to plant surfaces and uptake through stomata, and indirectly, by mitigation of theurban heat island intensity by canopy transpiration and building shading, that lowers the activity of chemicalreactions that led to the formation of photochemical pollutants in air. This is of particular importanceespecially for those cities located in the Mediterranean Basin, whose urban vegetation is often characterizedby VOC-emitting species that can contribute significantly to the O3 formation and destruction dynamics. Theaim of this paper is to present a short review of ecological research performed on vegetation of themetropolitan area of Rome, at different spatial and temporal scale, in order to evaluate the functional role ofurban green to monitor and improve urban air quality. In the frame of the project HEREPLUS (EU FP7), all ofthis information, opportunely integrated with climatic and pollutant data, will be implemented in a GIS and,by the use of geo-statistical methods, the ameliorating effect of urban vegetation will be quantified andmapped.
Keywords: urban vegetation; air quality improvement; O3, PM; pollutants uptake; GIS